Influence of slaughtering procedure on bleeding efficiency and quality traits of breast muscle in commercial broiler chicken - Rassid, Norafiqah (2016)
White meat from broiler chicken is the most preferable source of protein and have high demands in Malaysia due to its affordable price compared to the red meat. Slaughter is probably the most important operation in the transformation of an animal into pieces fit for human consumption. The main purpose of effective and humane slaughtering is to remove blood as quickly as possible while optimized bleeding enhance the quality of meat during storage. Bleeding efficiency has been implicated in shelf life, microbiological quality and other physic chemical traits of meat and meat products. The objective of this study was to determine the effect of slaughtering procedure on physico-chemical traits of Pectoralis major muscle in commercial broiler chicken. A total of thirty broiler chickens with a mean live weight of 2.00-2.50 kg were randomly assigned to either one of the three groups each consisting of 10 birds. The three treatment groups are: T1 - halal slaughter; T2 - non-halal slaughter and T3 - decapitation. Bleeding efficiency of each individual bird was determined during 90 sec of bleeding period through differences in body weight before and after slaughtering. Following to that, representative muscle samples were dissected at 4 specific periods, which are, 0 day (immediately after evisceration), 1 day, 3 days, and 5 days post mortem to represent the unconditioned (pre-rigor), 1 day-conditioned (chilled), 3 day-conditioned and 5 day-conditioned samples, respectively. Water holding capacity, pH, shear force values and myofibrillar fragmentation index were assessed objectively. The experiment was of a completely randomized design (CRD). Data of the bleeding efficiency and drip loss were subjected to one-way analysis of variance (ANOVA). Data for color, shear force, MFI and cooking loss were subjected to analysis of variance for a repeated measures design. The results showed that bleeding efficiency of chickens slaughtered by halal method was significantly higher than those assigned to non-halal and decapitation. Additionally, the drip loss of Pectoralis major muscle obtained from the birds of T1 group was lower (p<0.05) than those of T2 and T3 at day 5 post mortem. The Pectoralis major muscle of T1 group showed lowest (p<0.05) ultimate pH than those of T2 and T3 after 5 days aging. Halal slaughter exhibited lower redness and yellowness than non-halal and decapitation. At day 5 of storage at 4ºC, the cooking loss of the Pectoralis major muscle of the birds of T1 group was lower (p<0.05) than those of T2. It can be concluded that halal slaughter method improve bleeding efficiency and some of the meat qualities such as water holding capacity, pH, and color.